CHRONOSTRATIGRAPHY OF LATE NEOGENE SEDIMENTS IN THE SOUTHERN NORTH SEA BASIN AND PALEOENVIRONMENTAL INTERPRETATIONS - Kuhlmann G.; Langereis C.; Meulenkamp J.; Wong T.; Munsterman D.; Jan van Leeuwen R.; Verreussel R. (My University, 2006)
A chronostratigraphic framework has been established for Upper Neogene sediments from the northern Netherlands offshore sector, southern North Sea. Data of dinoflagellate cysts, pollen and foraminifers from eight boreholes are integrated and the resulting biostratigraphic events are connected to an additionally retrieved paleomagnetic record. The sedimentary succession comprises at the base Late to Middle Miocene sediments and spans the Piacenzian to Gelasian stages, from 3.6 to 1.8 Ma, including the paleomagnetic Gauss–Matuyama boundary and the Olduvai subchron. Sedimentation rates vary between 30 cm/kyr in the lower part of the succession and reach up to 84 cm/kyr in the upper part. These rates are high enough to record short paleomagnetic events and for the first time the presence of the so-called X-event has been recorded and dated at around 2.44 Ma in a sedimentary setting. The name ‘North Sea event’ is proposed here. The paleoclimatic and paleoenvironmental information pictures the onset of Northern Hemisphere Glaciation and the subsequent intensification of glacial conditions with its impact on the North Sea sea region. The paleoenvironmental changes are characterised by a stepwise development and five successive intervals are distinguished. During the first interval, a warm climate and an open marine setting prevailed. The second interval is characterised by dominantly cold climatic conditions with occasional warmer periods. During the third interval, the environment became restricted marine and a stable freshwater layering occurred, which facilitated the development of sea-ice in the shallow sea. Within the fourth interval, extreme cold (arctic) conditions
Keywords: Neogene; Cenozoic::Neogene; Кайнозой::Неоген